2017
DOI: 10.1039/c7sm01170a
|View full text |Cite
|
Sign up to set email alerts
|

A dissipative particle dynamics simulation study on phase diagrams for the self-assembly of amphiphilic hyperbranched multiarm copolymers in various solvents

Abstract: Self-assembly of amphiphilic hyperbranched multiarm copolymers (HMCs) has shown great potential for preparing all kinds of delicate supramolecular structures in all scales and dimensions in solution. However, theoretical studies on the influencing factors for the self-assembly of HMCs have been greatly lagging behind. The phase diagram of HMCs in selective solvents is very necessary but has not been disclosed up to now. Here, the self-assembly of HMCs with different hydrophilic fractions in various solvents wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…Vesicle self-assembly via DPD While numerous DPD simulations of polymer vesicles have been achieved, 34,37,82 and much has been said about the equilibrium morphology of micellar polymer solutions, 35,83 the literature does not provide simple, universal relationships between model parameters and vesicle morphology. Indeed such an endeavor is complicated by the formation of neighboring metastable morphologies and defective states that have similar free energies.…”
Section: Results and Discussion: Validation Of Rdpdmentioning
confidence: 99%
“…Vesicle self-assembly via DPD While numerous DPD simulations of polymer vesicles have been achieved, 34,37,82 and much has been said about the equilibrium morphology of micellar polymer solutions, 35,83 the literature does not provide simple, universal relationships between model parameters and vesicle morphology. Indeed such an endeavor is complicated by the formation of neighboring metastable morphologies and defective states that have similar free energies.…”
Section: Results and Discussion: Validation Of Rdpdmentioning
confidence: 99%
“…This indicates that about 90 % of the reactive groups would still be available for further post-assembly functionalization with bioactive molecules to form multi-potent NPs that have the potential to target specific cells [68]. In addition, by keeping the Mw of the HBP constant, the experimentally derived Mw values, percentages of functionalized end groups, and measured NP diameters provide valuable input parameters for stochastic simulation techniques such as dissipative particle dynamics [56,69]. These methods, to some extent, would allow for prediction of the impact of postgrafting hydrophobic and/or hydrophilic molecules on the surface of the NPs, but this will need further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The self‐assembly process of amphiphilic, hyperbranched, multi‐arm copolymers (HMCs) has also been simulated using DPD. [ 60–65 ] The degree of branching greatly influences the self‐assembled structure of HMCs. With the aid of DPD simulations, the study of different branching conditions revealed the self‐assembly mechanism and the kinetic formation process.…”
Section: Application Of Dpd On Mesoscale Properties Of Polymermentioning
confidence: 99%
“…The transformation of the polymer morphology from spherical to helical micelles was observed. [ 61 ] DPD can be employed to reveal the self‐assembly mechanisms of polymers and predict their new self‐assembled morphology. The self‐assembly behavior of multilayer onion‐like vesicles has been systematically investigated as well.…”
Section: Application Of Dpd On Mesoscale Properties Of Polymermentioning
confidence: 99%